Fabrication of a colorimetric sensor using acetic acid-capped drug-mediated copper oxide nanoparticles for nitrite biosensing in processed food - Nishan, Umar; Rehman, Sajida; Ullah, Riaz; Bari, Ahmed; Afridi, Saifullah; Shah, Mohibullah; Iqbal, Jibran; Asad, Muhammad; Badshah, Amir; Khan, Naeem; Hwang, In Min; Khan, Hameed Ullah; et al. (Frontiers in Materials, 2023)
Nitrite (NO2−) and nitrate (NO3−) are frequently used in cured meat products as preservatives, which give a better taste and work well in color fixation. As a key possible carcinogen, excessive dietary consumption of NO2− in cured meat products would be alarming to good health. Herein, copper oxide nanoparticles (CuO NPs) were synthesized using the drug Augmentin as a reducing and capping agent. The desired CuO NPs synthesis was confirmed by various characterization techniques, including UV-Visible spectroscopy, Fourier transform infrared spectroscopy (FTIR), EDX, TGA, X-ray diffraction, and SEM. The new approach of drug mediated CuO NPs capped acetic acid was developed for simple colorimetric detection of nitrite ions in a mimic solution of processed food. The color of the detection system changes from brown to yellow with the increase in concentration of NO2− and has been observed with naked eyes. The selectivity of the NO2− detection system by UV-Visible spectrum and naked eyes is compared to other ions such as Br-, I-, Cl-1, PO4-3, CO32-, SO42-. The platform was successfully employed for the determination of nitrite in real samples. Moreover, this probe can be used for the sensitive detection of the NO2− with a linear range of 1x10-8 to 2.40 x 10-6 M, a detection limit of 2.69 x 10-7 M, a limit of quantification 8.9x10-7 M, and a regression coefficient (R2) of 0.997. Our results suggest that this sensor can be used for on-site analysis and quantification as well as in the fields of disease diagnosis, environmental monitoring, and food safety.